Metabolism of arginine in juvenile largemouth bass (Micropterus salmoides) after oral or intraperitoneal administration of arginine or its substrates - Jiteng Wang; Jingyi Zhang; Xinyu Li; Hanying Y. Xu; Yeshun Yang; Jiankun Zhang; Wenping Feng; Qiang Chen; Fen Dong; Tao Han (Amino Acids)
Abstract The main objective of this experiment was to study the metabolism of arginine in juvenile largemouth bass (Micropterus salmoides). A total of 300 healthy fish (average weight of 25 ± 0.5 g) were randomly assigned to ten groups. Experimental fish were orally administered or intraperitoneally injected with 0.9% sodium chloride, arginine, arginine-aspartate, citrulline, and glutamate solutions, respectively. They were euthanized at 10, 30, 60, 120, and 240 min after oral administration or intraperitoneal injection, and various tissue samples were subsequently collected for analysis. The results revealed that serum ornithine and citrulline concentrations of largemouth bass were significantly increased by oral administration of arginine or arginine-aspartate (P < 0.05). Intraperitoneal injection of arginine or arginine-aspartate solution significantly elevated the concentrations of ornithine and citrulline in the serum, liver, kidney, and muscles (P < 0.05). The concentrations of citrulline, ornithine, and arginine in serum and muscle increased significantly at 4 h after intraperitoneal injection of glutamate (P < 0.05). Intraperitoneal injection of citrulline significantly increased the concentrations of ornithine and arginine in the serum and muscles (P < 0.05). The research findings demonstrate that both free and small peptide forms of arginine were rapidly degraded to ornithine due to the high arginase activity in various tissues of largemouth bass. Additionally, the pathway of synthesizing citrulline from glutamate and then arginine from citrulline may exist in largemouth bass, but the exact location of this synthesis process may differ from that found in mammals.